Southernmost dermochelyid turtle from the miocene - Sterli, Juliana (2025)
Dermochelyids are a unique lineage of turtles where the primary carapace underwent an extreme reduction, with its maximum expression in the extant Dermochelys coriacea. Above the primary carapace (thecal), a secondary (epithecal) carapace formed by thousands of ossicles appeared in the late Paleocene. In general, the fossil record of dermochelyids is incomplete, fragmentary, and patchy. Besides, no in depth and detailed studies on their anatomy led to a poorly resolved alpha taxonomy. In this contribution, we present one of the most complete dermochelyids in the world. Our new turtle was found in the Gaiman Formation (Lower Miocene) in Chubut, Argentina. This Burdigalian record of Patagonia represents the southernmost species in the fossil record of dermochelyid turtles in the Southern Hemisphere in the Miocene. The histological analysis of long bones shows a highly remodeled cortex, a unique condition in turtles. The tissue compaction recorded in this new turtle would suggest it was a very old individual. The phylogenetic analysis recovered the new species in a clade characterized by longitudinal ridges in the carapace and ossicles arranged in a “sunflower” pattern. Exploring the diversity patterns of dermochelyids, we recognize two peaks of diversity and three extinction events, comparable with those observed in other marine tetrapods (e.g., cetaceans, penguins).